Sedimentation study of the Yazoo River Basin. User's manual for the Yazoo Data Storage and Retrieval System - Simons, D. B., author; Li, R. M., author; Duong, N., author; Civil Engineering Department, Engineering Research Center, Colorado State University, publisher (Colorado State University. Libraries, 1978)
This manual describes the Yazoo Data Storage and Retrieval System (YAZBD). This system was developed as part of the Phase I - Sedimentation Study of the Yazoo River Basin. The system enables users with varying amounts of computer experience to efficiently access, retrieve, store, and analyze large amounts of hydraulic and hydrological data from the Yazoo Basin. Volume I of this manual is designed for general users. It concentrates on accessing, retrieving, and analyzing data. Volume II is intended for the system analysts and/or data managers. Included are details of program execution, input and output, data updating, flowcharts, variable definitions, and hardware and software requirements.
User's manual for the Yazoo Data Storage and Retrieval System
CER78-79DBS-RML-ND20.
October 1978.
Prepared for U.S. Army Corps of Engineers, Vicksburg District, Vicksburg, Mississippi.
Keywords: Sedimentation and deposition -- Mississippi -- Yazoo River; Yazoo River Watershed (Miss.)